Optimalisasi Hasil Belajar Siswa Melalui Penerapan Model Pembelajaran Kooperatif Tipe VAK (Visual, Auditori, Kinestetik) - Setiawan, Anderi; Jamal, M. Arifuddin; Suriasa, Suriasa (Universitas Lambung Mangkurat, 2015)
The studentÂ learning results that low were indicated because the less of using innovative learning that make the lack of students response in asking and responding to questions. These research aims to optimize student learning results of clss IX C SMP Negeri 27 Banjarmasin at the dynamic electrical subject through the application of cooperative learning type VAK. The specific purposes of this research were to describe: (1) adherence of the lesson plans, (2) student activities, (3) the student learning results, and (4) the studentâs responses toward teaching and learning proces. These research were classroom action research that consists of 3 cycles. CollectingÂ data through observation, study test results, observations, questionnaires, and documentation. TheÂ results wereÂ analyzed byÂ descriptive qualitative and quantitative. The results of this research were: (1) an increase in the percentage of adherence to the RPP in each cycle with the very well category, (2) the activity of student were categorized very well, (3) the results of student learning in the first cycle has not been completed in the classical completeness, in cycle II and III increased classically with complete categoy, (4) the studentâs responses toward teacingÂ and learning proces were very well category. Based on the findings were obtained the conclusion that the student learning result of class IX C SMP Negeri 27 Banjarmasin on the dynamic electrical subjectÂ can be optimized by the application of cooperative learning type VAK.Â